THE LANDSAT 7 ETM+ REMOTE SENSING IMAGERY FOR LITHOLOGICAL AND STRUCTURAL MAPPING IN THE CENTRAL CÔTE D’IVOIRE (WEST AFRICA): CASE OF DABAKALA AREA - Allou, Gnanzou; Ouattara, Gbele; Coulibaly, Yacouba; Bonin, Bernard (European Scientific Journal, ESJ, 2015)
The control of different faults networks is a capital tool, due to the fact that any fault zone is dependent on the possibility of concentration of useful minerals such as gold. Also, it is clear that most of the identified faults date for most long time and it is imperative to update structural maps. From remote sensing from Landsat 7 ETM+ of Dabakala area (Central Côte d’Ivoire), we extracted lineaments from an analogical analysis supplemented by numerical analyzes using directional filters and textures. Subsequently, we determined the limits of the lithological units from their textures and colors. All news faults obtained were incorporated into the existing ones. The assimilation of some lineaments fractures and faults was made on the basis of pre-existing map data and field observations. A sketch lithostructural map was also obtained. Regarding lithological distinctions, eleven optically distinct zones, categorized into three main provinces, have been identified. Several major faults directions were mapped. These are the mostly N-S to NNE-SSW with sinistral, dextral N90° to N100° direction and dextral or sinistral NW-SE to NNW-SSE direction. A significant structure appears on the Landsat ETM+ colored composition of ACPs Band Ratios 5-7/3-5/3-2. This is the Sarala fault (FSr), with N075° to N080° direction, which is identified for the first time. Other structures appear on the processed images should be checked in the field